Naringin a potent antioxidant used as bioavailibility enhancer for terbinafine hydrochloride - Singh, Akanksha; Juyal, Divya; Singh, Vikram; Rawat, Geeta (Journal of Applied Pharmaceutical Research, 2014)
The poor bioavailability of drugs has been identified as the single most important challenge in oral drug delivery. Prominent among the factors responsible for this are the oxidative metabolic activity of the intestinal and hepatic cytochrome P450 enzyme family. Naringin and naringenin which are the major phytochemical component of grapefruit juice, a well-known cytochrome P450 3A4 inhibitor and flavone glycoside, is antioxidant in nature and occurs naturally in the pericarp of citrus fruit, and particularly of grapefruit (Citrus paradisii) where it is the predominant flavonoid found and is responsible for the bitter taste associated with the fruit. CYP3A4 which is a class of CYP – 450 (microsomal enzyme) is responsible for the oxidative metabolic reaction of various substrates which decreases the bioavailability of drug.